A MOFs-derived electromagnetic wave absorbing material, preparation method and application

By designing a solution of cobalt acetate and/or zinc acetate and dimethylimidazole, forming an accordion-like MOFs precursor and carbonizing at high temperature, accordion-like MOFs derived electromagnetic wave absorption materials are prepared, which solves the problems of impedance mismatch of existing carbon materials in the field of electromagnetic wave absorption and complex preparation processes, and achieves efficient electromagnetic wave absorption performance and low-cost preparation.

CN119029564BActive Publication Date: 2025-04-04XIAN AIRCRAFT DESIGN INST OF AVIATION IND OF CHINA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411492460.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-04-04
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

In the field of electromagnetic wave absorption, existing carbon materials have problems such as high dielectric constant, impedance mismatch, serious electromagnetic wave reflection, complex preparation process, high cost, and environmental pollution, and it is difficult to achieve the characteristics of strong absorption and bandwidth at the same time.

Method used

By designing a solution of cobalt acetate and/or zinc acetate and dimethylimidazole, an accordion-like MOFs precursor is formed, and carbonized at high temperature under the mixed gas conditions of H2 and N2, an accordion-like MOFs-derived electromagnetic wave absorbing material is prepared. This method combines porous structure and electromagnetic synergistic enhancement, and controls the electromagnetic wave absorption performance of the material by regulating the metal ion ratio and carbonization conditions.

Benefits of technology

The effective combination of electromagnetic coordination and porous structure is achieved, which reduces the preparation cost and environmental pollution, and can achieve the maximum absorption intensity of electromagnetic waves below -50dB and the effective absorption bandwidth is greater than 7GHz at a lower filling amount.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119029564B_ABST
    Figure CN119029564B_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of electromagnetic wave absorbing materials, and particularly relates to a MOFs-derived electromagnetic wave absorbing material, a preparation method and an application. The preparation method comprises: step S1, dissolving cobalt acetate and / or zinc acetate in deionized water and stirring evenly at room temperature to form solution A, dissolving dimethylimidazole in deionized water and stirring evenly at room temperature to form solution B, pouring solution B into solution A and stirring, and obtaining an accordion-shaped MOFs precursor by centrifugal drying; step S2, subjecting the accordion-shaped MOFs precursor to high-temperature carbonization treatment under the conditions of a mixture of H2 and N2 to obtain an accordion-shaped MOFs-derived electromagnetic wave absorbing material. The preparation process of the present application is simple, low-cost, and the preparation process does not use materials that pollute the environment. The prepared electromagnetic wave absorbing material can simultaneously achieve an effective combination of electromagnetic synergy and porous structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of electromagnetic wave absorbing materials, and in particular, relates to a MOFs-derived electromagnetic wave absorbing material, a preparation method and an application thereof. Background Art

[0002] Electromagnetic synergistic enhancement and porous structure are two key factors in the preparation of lightweight and efficient electromagnetic wave absorbing materials. Carbon materials have the characteristics of light weight, thin thickness, good stability, etc., and have potential application value in the field of electromagnetic wave absorption. However, the dielectric constant of carbon materials is relatively high, and the impedance between them and air is not matched. Electromagnetic waves are easily reflected on their surface and it is difficult for them to be incident on the material and absorbed. Secondly, the loss mechanism of electromagnetic wave absorption of a single carbon material is relatively single, and it is difficult to achieve the characteristics of strong absorption and wide bandwidth at the same time. Therefore, composite materials that have both electromagnetic synergistic enhancement and porous structure have attracted much attention in the field of electromagnetic wave absorbing materials.

[0003] In recent years, the research on the use of high-temperature carbonized metal-organic frameworks (MOFs) to prepare lightweight and efficient electromagnetic wave absorbing materials has attracted widespread attention from researchers. Through the design of metal ions and organic ligands, high-temperature carbonization can achieve an effective combination of porous structure and electromagnetic synergy. Organic ligands are carbonized at high temperature to form a carbon matrix with micropores as the main component, and metal ions are carbonized and reduced to magnetic metal particles embedded in the carbon matrix to achieve electromagnetic synergy enhancement. For example, Ji Guangbin's research group carbonized Co x Ni y -MOFs nanosheets introduce magnetic particles into the porous carbon structure and regulate Co 2+ and Ni 2+ There is no doubt that this method can greatly improve the electromagnetic wave absorption performance of MOFs-derived materials to a certain extent, but there are still problems such as complex preparation process, difficult porous structure regulation, high cost, and the use of toxic solvents in the preparation process, which causes environmental pollution. Summary of the invention

[0004] The purpose of the present application is to provide a MOFs-derived electromagnetic wave absorbing material, a preparation method and an application thereof.

[0005] The first aspect of the present application provides a method for preparing a MOFs-derived electromagnetic wave absorbing material, mainly comprising:

[0006] Step S1, dissolving cobalt acetate and / or zinc acetate in deionized water and stirring evenly at room temperature to form a solution A, dissolving dimethylimidazole in deionized water and stirring evenly at room temperature to form a solution B, pouring the solution B into the solution A and stirring, and obtaining an accordion-shaped MOFs precursor by centrifugal drying;

[0007] Step S2, the accordion-shaped MOFs precursor is heated in H 2 With N 2 High-temperature carbonization treatment is carried out under mixed gas conditions to obtain accordion-shaped MOFs-derived electromagnetic wave absorbing materials.

[0008] Preferably, in step S1, when cobalt acetate or zinc acetate is used alone, the molar amount of each portion of cobalt acetate or zinc acetate is 1-3 mmol, when a mixture of cobalt acetate and zinc acetate is used, the molar amount of each portion of the mixture is 0.5-2 mmol, and the molar ratio of the two is 1:0.5-2, the molar amount of dimethylimidazole corresponding to each portion of cobalt acetate, zinc acetate or the mixture is 20-30 mmol, and the corresponding volumes of deionized water in solution A and solution B are both 30-60 mL.

[0009] Preferably, in step S1, the room temperature is 20-30° C. and the stirring time is 20-30 h.

[0010] Preferably, in step S1, the room temperature is 20°C and the stirring time is 30 hours.

[0011] Preferably, in step S1, the room temperature is 30° C. and the stirring time is 20 h.

[0012] Preferably, in step S1, the room temperature is 25°C and the stirring time is 25h.

[0013] Preferably, in step S2, 2 With N 2 In the mixed gas, H 2 The volume fraction is 5~20%.

[0014] Preferably, in step S2, the heating rate of the high temperature carbonization is 1-4°C / min, the temperature is 700-900°C, and the time is 2-4h.

[0015] Preferably, in step S2, the high temperature carbonization is carried out at a heating rate of 2°C / min, a temperature of 800°C and a time of 3h.

[0016] The second aspect of the present application provides a MOFs-derived electromagnetic wave absorbing material prepared by the method described above.

[0017] The third aspect of the present application provides an application of the electromagnetic wave absorbing material as described above in the preparation of an electromagnetic absorber, or in dealing with electromagnetic wave radiation and pollution.

[0018] The preparation process of the present application is simple and low in cost. No materials that pollute the environment are used in the preparation process. The prepared electromagnetic wave absorbing material can simultaneously achieve an effective combination of electromagnetic synergy and porous structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a flow chart of a preferred embodiment of the method for preparing the MOFs-derived electromagnetic wave absorbing material of the present application.

[0020] Figure 2 It is the X-ray diffraction pattern of the samples prepared in the three embodiments of the present application.

[0021] Figure 3 These are SEM and TEM images of the samples prepared in Examples 1 to 3 of the present application, wherein Figure (a), Figure (c), and Figure (e) are SEM images of the samples prepared in Examples 1 to 3, respectively, and Figure (b), Figure (d), and Figure (f) are TEM images of the samples prepared in Examples 1 to 3, respectively.

[0022] Figure 4 is the N of the samples prepared in Examples 1 to 3 of the present application 2 Adsorption-desorption isotherms and pore size distribution diagrams, where (a) is N 2 Adsorption-desorption isotherm; Figure (b) is the pore size distribution curve.

[0023] Figure 5 It is a graph of electromagnetic wave reflection loss when the samples prepared in Examples 1 to 3 are filled in a paraffin matrix at a content of 20 wt%, wherein Figure (a) corresponds to Example 1; Figure (b) corresponds to Example 2; and Figure (c) corresponds to Example 3. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical scheme and advantages of the implementation of this application clearer, the technical scheme in the implementation of this application will be described in more detail in combination with the drawings in the implementation of this application. In the drawings, the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The described implementation is a part of the implementation of this application, not all of the implementations. The implementation described below with reference to the drawings is exemplary and is intended to be used to explain this application, and cannot be understood as a limitation on this application. Based on the implementation in this application, all other implementations obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application. The implementation of this application is described in detail below in combination with the drawings.

[0025] The first aspect of the present application provides a method for preparing a MOFs-derived electromagnetic wave absorbing material, such as Figure 1 As shown, it mainly includes:

[0026] Step S1, dissolving cobalt acetate and / or zinc acetate in deionized water and stirring evenly at room temperature to form a solution A, dissolving dimethylimidazole in deionized water and stirring evenly at room temperature to form a solution B, pouring the solution B into the solution A and stirring, and obtaining an accordion-shaped MOFs precursor by centrifugal drying;

[0027] Step S2, the accordion-shaped MOFs precursor is heated in H 2 With N 2 High-temperature carbonization treatment is carried out under mixed gas conditions to obtain accordion-shaped MOFs-derived electromagnetic wave absorbing materials.

[0028] Compared with the sheet-like porous nanocomposite material synthesized by thermal reduction and prepared by acid etching, the preparation mechanism of the present application is different. The boiling points of different metals formed by thermal reduction during the high-temperature carbonization process are different. By controlling the temperature and reducing atmosphere, an electromagnetic wave absorbing material with both porous structure and electromagnetic synergistic enhancement is formed. Specifically, the carbon nanotubes formed by magnetic particle catalysis are used to increase the conduction loss of the electromagnetic wave absorbing material; the structure of the accordion sheet precursor is used to increase the interface polarization loss of the electromagnetic wave absorbing material; the mesoporous defects generated by the thermal decomposition of metal Zn are used to enhance the defect polarization of the electromagnetic wave absorbing material; the heterogeneous interface between the magnetic particle Co, carbon nanotubes and carbon matrix is ​​used to improve the impedance matching of the electromagnetic wave absorbing material to achieve electromagnetic synergistic enhancement; the sheet-like multilayer structure of the electromagnetic wave absorbing material is used to achieve its multi-scattering effect on electromagnetic waves.

[0029] The electromagnetic wave absorbing material prepared in the present application has the characteristics of an accordion sheet structure, and the number of stacked layers is greater than 10.

[0030] The electromagnetic wave absorbing material prepared in the present application has a dual pore size distribution characteristic with micropores as the main pore size distribution, the pore size distribution of the micropores is between 1 and 2 nm, and the pore size distribution of the mesopores is between 2 and 5 nm.

[0031] The electromagnetic wave absorbing material prepared in the present application has multi-walled carbon nanotubes generated in situ on its surface and has obvious mesoporous holes, and precise control of the mesoporous structure can be achieved without the need for additional acid-base etching.

[0032] The electromagnetic wave absorption material prepared in the present application has good interface polarization, impedance matching and electromagnetic synergistic enhancement effect. At a lower filling amount, the maximum absorption intensity of electromagnetic waves is lower than -50dB, and the effective absorption bandwidth is greater than 7GHz.

[0033] In some optional embodiments, in step S1, when cobalt acetate or zinc acetate is used alone, the molar amount of each portion of cobalt acetate or zinc acetate is 1-3 mmol, and when a mixture of cobalt acetate and zinc acetate is used, the molar amount of each portion of the mixture is 0.5-2 mmol, and the molar ratio of the two is 1:0.5-2. The molar amount of dimethylimidazole corresponding to each portion of cobalt acetate, zinc acetate or the mixture is 20-30 mmol, and the corresponding volumes of deionized water in solution A and solution B are both 30-60 mL.

[0034] In some optional embodiments, in step S1, the room temperature is 20-30° C., and the stirring time is 20-30 h.

[0035] In some optional embodiments, in step S1, the room temperature is 20°C and the stirring time is 30 hours.

[0036] In some optional embodiments, in step S1, the room temperature is 30° C. and the stirring time is 20 h.

[0037] In some optional embodiments, in step S1, the room temperature is 25°C and the stirring time is 25 hours.

[0038] In some optional embodiments, in step S2, 2 With N 2 In the mixed gas, H 2 The volume fraction is 5~20%.

[0039] In some optional embodiments, in step S2, the heating rate of the high temperature carbonization is 1-4°C / min, the temperature is 700-900°C, and the time is 2-4h.

[0040] In some optional embodiments, in step S2, the high temperature carbonization is carried out at a heating rate of 2°C / min, a temperature of 800°C, and a time of 3 hours.

[0041] With respect to the three methods for preparing solution A given in step S1 (using cobalt acetate alone, using zinc acetate alone, and using a mixture of the two to prepare a solution), combined with the parameter ranges given in the above embodiments, a comparative description is given through the following three specific embodiments.

[0042] Embodiment 1:

[0043] 2 mmol of cobalt acetate was dissolved in 40 mL of deionized water and stirred at room temperature to form solution A; 24 mmol of dimethylimidazole was dissolved in 40 mL of deionized water and stirred at room temperature to form solution B; solution B was quickly poured into solution A and stirred continuously at 25 °C for 24 h. The accordion-shaped Co-MOFs precursor was obtained by centrifugal drying; the mixture was heated in a mixed atmosphere (10% H 2 +90%N 2 ) and annealed at 800 °C for 3 h in a tube furnace at a heating rate of 2 °C / min to obtain an accordion-shaped MOFs-derived porous magnetic electromagnetic wave absorbing material.

[0044] Embodiment 2:

[0045] 1 mmol of cobalt acetate and 1 mmol of zinc acetate were dissolved in 40 mL of deionized water and stirred at room temperature to form solution A; 24 mmol of dimethylimidazole was dissolved in 40 mL of deionized water and stirred at room temperature to form solution B; solution B was quickly poured into solution A and stirred continuously at 25 °C for 24 h. The accordion-shaped CoZn-MOFs precursor was obtained by centrifugal drying; the mixture was heated to 40 °C in a mixed atmosphere (10% H 2 +90%N 2 ) and annealed at 800 °C for 3 h in a tube furnace at a heating rate of 2 °C / min to obtain an accordion-shaped MOFs-derived porous magnetic electromagnetic wave absorbing material.

[0046] Embodiment 3:

[0047] 2 mmol of zinc acetate was dissolved in 40 mL of deionized water and stirred at room temperature to form solution A; 24 mmol of dimethylimidazole was dissolved in 40 mL of deionized water and stirred at room temperature to form solution B; solution B was quickly poured into solution A and stirred continuously at 25 °C for 24 h. Accordion-shaped Zn-MOFs precursor was obtained by centrifugal drying; the precursor was heated in a mixed atmosphere (10% H 2 +90%N 2 ) and annealed at 800 °C for 3 h in a tube furnace at a heating rate of 2 °C / min to obtain an accordion-shaped MOFs-derived porous electromagnetic wave absorbing material.

[0048] The crystal structure, micromorphology, pore size distribution and electromagnetic wave absorption performance of the electromagnetic wave absorbing material obtained in this application were characterized. The results are as follows Figures 2~5 shown.

[0049] exist Figure 2 In the material prepared in Example 1, obvious diffraction peaks appear at 44.2°, 51.5° and 75.8°, corresponding to the (111), (200) and (220) crystal planes of magnetic Co (PDF#15-0806), respectively; in addition, the diffraction peak of the carbon-based material corresponding to about 26° is not obvious, which is mainly due to the strong diffraction peak of the magnetic Co particles. The diffraction peak of the material prepared in Example 2 is exactly the same as that in Example 1, indicating that the crystal structures of the two are the same. The material prepared in Example 3 only has an obvious broad diffraction peak at about 25.6°, corresponding to the diffraction peak of the carbon-based material (PDF#41-1487), indicating that there are no magnetic particles in the material. It can be seen from the X-ray diffraction spectrum that the chemical composition of the accordion-shaped MOFs-derived electromagnetic wave absorption material can be regulated by selecting Co / Zn ions.

[0050] Figure 3In the figure, Figure (a), Figure (c), and Figure (e) are SEM images of samples prepared in Examples 1 to 3, and Figure (b), Figure (d), and Figure (f) are TEM images of samples prepared in Examples 1 to 3. In Figures (a) and (b), the electromagnetic wave absorbing material prepared in Example 1 has an obvious accordion sheet structure, and a large number of carbon nanotubes are attached to the surface of the sheet structure. This is mainly due to the magnetic Co particles in H 2 The catalytic effect was observed under the conditions of 1.5 ℃ and 2.5 ℃, and the magnetic Co particles agglomerated, which was mainly due to the high content of magnetic Co particles. In Figures (c) and (d), the electromagnetic wave absorbing material prepared in Example 2 also had an accordion sheet structure, and the content of carbon nanotubes on its surface was significantly reduced, which was mainly due to the introduction of non-magnetic Zn 2+ ions, to some extent, reduce the catalytic effect of magnetic Co particles, the particle size of magnetic Co particles is reduced, no obvious agglomeration occurs, and some mesoporous holes appear on the surface of the accordion layer. In Figures (e) and (f), the electromagnetic wave absorbing material prepared in Example 3 also has an accordion sheet structure, with no carbon nanotubes on its surface and accompanied by obvious mesoporous holes, which is mainly due to the low melting point of metal Zn, which volatilizes during high-temperature carbonization.

[0051] Figure 4 N is the N of the samples prepared in Examples 1 to 3 of this application. 2 Adsorption-desorption isotherms and pore size distribution diagrams, where (a) is N 2 Adsorption-desorption isotherms; Figure (b) is the pore size distribution curve. As can be seen from Figure (a), the adsorption-desorption isotherms of the samples prepared in Example 2 and Example 3 show an upward trend in the low pressure zone, indicating that they both have a microporous structure, and the upward trend of the sample prepared in Example 3 is more obvious, indicating that its microporous structure is more obvious. In addition, between the relative pressure of 0.4-0.9, the samples prepared in Example 2 and Example 3 present a type IV adsorption isotherm, indicating that they have mesoporous structural characteristics. As can be seen from Figure (b), the sample prepared in Example 1 has obvious mesoporous structural characteristics, and its optimal pore size distribution is about 2.7nm; the samples prepared in Example 2 and Example 3 both have a microporous-mesoporous dual pore size distribution characteristic, and the optimal pore size distribution of Example 2 is 1.6nm and 3.4nm, respectively, and the optimal pore size distribution of Example 3 is 1.6nm and 2.9nm, respectively.

[0052] Figure 5The electromagnetic wave reflection loss diagram of the samples prepared in Examples 1 to 3 when the filling amount in the paraffin matrix is ​​20wt%, wherein Figure (a) corresponds to Example 1; Figure (b) corresponds to Example 2; Figure (c) corresponds to Example 3. In the thickness range of 1mm-4mm, the maximum reflection loss of the sample prepared in Example 1 is -19.57dB, and the effective bandwidth below -10dB is less than 6GHz; the maximum reflection loss of the sample prepared in Example 2 is -52.3dB, and the effective bandwidth below -10dB is 7.7GHz; the maximum reflection loss of the sample prepared in Example 3 is -24.4dB, and the effective bandwidth below -10dB is 6.2GHz. It can be seen from the electromagnetic wave reflection loss spectrum that by adjusting the content of Co / Zn ions, the electromagnetic wave absorption performance of the accordion-shaped MOFs-derived electromagnetic wave absorption material can be regulated.

[0053] The second aspect of the present application provides a MOFs-derived electromagnetic wave absorbing material prepared by the method described above.

[0054] The third aspect of the present application provides an application of the electromagnetic wave absorbing material as described above in the preparation of an electromagnetic absorber, or in dealing with electromagnetic wave radiation and pollution.

[0055] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.

Claims

1. A method for preparing a MOFs-derived electromagnetic wave absorbing material, characterized in that: include: Step S1, dissolving cobalt acetate and zinc acetate in deionized water and stirring at room temperature to form solution A, dissolving dimethylimidazole in deionized water and stirring at room temperature to form solution B, pouring solution B into solution A and stirring, and obtaining an accordion-shaped MOFs precursor by centrifugal drying; Step S2, subjecting the accordion-shaped MOFs precursor to high-temperature carbonization treatment under a mixture of H2 and N2 to obtain an accordion-shaped MOFs-derived electromagnetic wave absorbing material; The molar amount of the mixture of cobalt acetate and zinc acetate is 0.5-2 mmol, the molar ratio of the two is 1:0.5-2, the molar amount of dimethylimidazole corresponding to each mixture is 20-30 mmol, the volume of deionized water of the corresponding solution A and solution B is 30-60 mL, and the volume fraction of H2 in the mixed gas of H2 and N2 is 10%-20%; Wherein, in step S1, the room temperature is 20-30°C, and the stirring time is 20-30h; in step S2, the heating rate of the high-temperature carbonization is 1-4°C / min, the temperature is 700-900°C, and the time is 2-4h.

2. The method for preparing the MOFs-derived electromagnetic wave absorbing material according to claim 1, characterized in that: In step S1, the room temperature is 20°C and the stirring time is 30 hours.

3. The method for preparing the MOFs-derived electromagnetic wave absorbing material according to claim 1, characterized in that: In step S1, the room temperature is 30° C. and the stirring time is 20 h.

4. The method for preparing the MOFs-derived electromagnetic wave absorbing material according to claim 1, characterized in that: In step S1, the room temperature is 25°C and the stirring time is 25h.

5. The method for preparing the MOFs-derived electromagnetic wave absorbing material according to claim 1, characterized in that: In step S2, the high temperature carbonization is carried out at a heating rate of 2°C / min, a temperature of 800°C, and a time of 3 hours.

6. A MOFs-derived electromagnetic wave absorbing material, characterized in that: Prepared by the method according to any one of claims 1 to 5.

7. Use of the electromagnetic wave absorbing material as claimed in claim 6, characterized in that: Application in the preparation of electromagnetic absorbers, or in dealing with electromagnetic wave radiation and pollution.

Citation Information

Patent Citations

  • Multifunctional electromagnetic material with characteristics of high-frequency electromagnetic absorption and corrosion resistance as well as preparation method and application of multifunctional electromagnetic material

    CN115831515A

  • ZIF-8 material and preparation system and preparation method therefor, monatomic catalyst, battery separator and use

    WO2023245622A1